Maintenance Treatment With Low-Dose Decitabine After Allogeneic Hematopoietic Cell Transplantation in Patients With Adult Acute Lymphoblastic Leukemia - Liu, Jia; Jiang, Zhong-Xing; Xie, Xin-Sheng; Wan, Ding-Ming; Cao, Wei-Jie; Wang, Meng; Liu, Zhen-Zhen; Dong, Zhen-Kun; Wang, Hai-Qiong; Lu, Run-Qing; Zhang, Yin-Yin; Cheng, Qian-Qian; et al. (Frontiers in Oncology, 2021)
Background: Post-transplant relapse remains to be one principal leading cause of failure after allogeneic hematopoietic stem cell transplantation (allo-HSCT) in patients with adult acute lymphoblastic leukemia (ALL). The aim of this study was to investigate the efficacy and safety of low-dose decitabine on the prevention of adult ALL relapse after allo-HSCT. Methods: In this prospective study, we enrolled 34 patients with ALL who underwent allo-HSCT from August 2016 to April 2020 and gave them low-dose decitabine maintenance treatment after transplantation. Relapse, graft-versus-host disease (GVHD) and overall survival (OS) were observed, and the safety of the regimen was evaluated. Results: Among the enrolled 34 patients, 32 patients (94.1%) developed only grade I-II myelosuppression, 6 patients relapsed and 6 patients died. The 2-year cumulative incidence of relapse rate (CIR), OS and disease-free survival (DFS) were 20.2%, 77.5% and 73.6%, respectively. The 2-year CIR, OS and DFS of 12 patients with T-ALL/Lymphoblastic Lymphoma (LBL) were 8.3%, 90% and 81.5%, respectively. Among the 7 patients with T-ALL, no one relapsed. During maintenance treatment, only 1 patient (2.9%) developed grade IV acute GVHD and 4 (11.8%) patients had severe chronic GVHD. Conclusions: Maintenance treatment with low-dose decitabine after allo-HSCT was associated with good tolerance, a low relapse rate without significantly affecting GVHD, and satisfactory survival in patients with ALL, especially patients with T-ALL. Clinical Trial Registration: Chinese Clinical Trials Registry, identifier ChiCTR1800014888.